Radiographic comparison of cross‐sectional lumbar pedicle fill when placing screws with navigation versus free‐hand technique. Issue 2 (4th May 2015) - Pirris, Stephen M.; Nottmeier, Eric W.; O'Brien, Michael; Rahmathulla, Gazanfar; Pichelmann, Mark
Abstract: Background: Pedicle screws are often used for spinal fixation. Increasing the percentage of pedicle that is filled with the screw presumably yields greater fixation. It has not been shown whether spinal navigation helps surgeons more completely fill their instrumented pedicles. Methods: Fifty consecutive patients from each arm (navigated and free‐hand) were retrospectively reviewed. The cross‐sectional area of each instrumented lumbar pedicle and screw were measured using an automatic area calculation tool. The coronal images and measurements were blinded to the surgeons. Results: The instrumented pedicles in the navigated patients were significantly more filled by screws than the pedicles in the non‐navigated patients (P < 0.001). Conclusion: Obtaining a higher cross‐sectional percentage fill of the pedicle with a screw is expected to provide greater spinal fixation in instrumented fusion surgery. This study shows that utilizing spinal navigation helps to more completely fill the pedicles that are being instrumented. Copyright © 2015 John Wiley & Sons, Ltd.